Seasonal rainfall regime modulates genetic variation in the moss Pseudocrossidium crinitum - Wilding, Nicholas (Department of Biological Sciences, 2017)
Patterns of genetic variation, resulting from Pliocene-Pleistocene climate shifts have been largely documented for species from Europe. However, little is known from Africa and especially South Africa, where climate shifts have often been invoked to explain the amazingly high diversity of the Cape Floristic Region. An analysis of cpDNA and nDNA sequence variation for 65 populations of the moss Pseudocrossidium crinitum across South Africa revealed the presence of a phylogeographic break corresponding to the split between the winter-rainfall zone (WRZ) and the all-year-(ARZ) and summer-rainfall zones (SRZ). Coalescent estimates of the time since these populations split (1.3 - 3.4 Mya) are highly consistent with the onset of winter-rainfall in the south-western Cape. Estimates of gene flow indicate much higher levels of gene flow into the WRZ, fitting the expected direction of gene flow based on wind patterns and differences in phenology. Haplotype diversity was observed to be highest in the WRZ, suggesting a number of genetic structuring factors in play within the WRZ. Additional analysis of populations from Chile and Lesotho suggest recent dispersal from Chile and possibly high levels of trans-continental gene flow between these populations. The study provides a first look at the genetic consequences of paleo-climate shifts on a moss species in South Africa. These results, in combination with other similar studies, may help to piece together the factors and processes responsible for the high diversity in the CFR today.